2022
DOI: 10.1186/s13287-022-02983-0
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells-derived small extracellular vesicles alleviate diabetic retinopathy by delivering NEDD4

Abstract: Background As a leading cause of vision decline and severe blindness in adults, diabetic retinopathy (DR) is characterized by the aggravation of retinal oxidative stress and apoptosis in the early stage. Emerging studies reveal that mesenchymal stem cells-derived small extracellular vesicles (MSC-sEV) treatment represents a promising cell-free approach to alleviate ocular disorders. However, the repairing effects of MSC-sEV in DR remain largely unclear. This study aimed at exploring the role an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 45 publications
0
25
0
1
Order By: Relevance
“…Figure 2 illustrates the basic process of obtaining MSC-EVs and also their applications in MetS. Table 1 summarises the comprehensive studies conducted in either vitro or vivo that revealed the potential of MSC-EVs therapy in normalising metabolic parameters of MetS subjects [15][16][17][18][19][20][21] ; These studies demonstrate that MSC-EVs derived from various sources possess the ability to promote cell proliferation, migration and multipotent differentiation.…”
Section: Relevance Of Msc-derived Evs For Metabolic Syndrome Therapymentioning
confidence: 99%
See 3 more Smart Citations
“…Figure 2 illustrates the basic process of obtaining MSC-EVs and also their applications in MetS. Table 1 summarises the comprehensive studies conducted in either vitro or vivo that revealed the potential of MSC-EVs therapy in normalising metabolic parameters of MetS subjects [15][16][17][18][19][20][21] ; These studies demonstrate that MSC-EVs derived from various sources possess the ability to promote cell proliferation, migration and multipotent differentiation.…”
Section: Relevance Of Msc-derived Evs For Metabolic Syndrome Therapymentioning
confidence: 99%
“…MSC-EVs efficacy in MetS, such as hypertension, diabetic retinopathy, renal damage, fatty liver disease and diabetes mellitus have been demonstrated in many studies. [15][16][17][18][19][20][21] MSCs, mesenchymal stem cells; MSC-EV, MSCs derived extracellular vesicles; NAFLD, nonalcoholic fatty liver disease; NASH, nonalcoholic steatohepatitis.…”
Section: Pathophysiology and Underlying Factors Contributing To Metab...mentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, researchers have focused on the exploration of functional components within MSC-EVs in diabetic retinopathy therapy. For example, the results of Sun et al have shown that hyperglycemia-induced upregulation of phosphatase and tensin homolog (PTEN) can inhibit AKT phosphorylation and nuclear factor erythroid 2-related factor 2 (NRF2) expression in retinal tissues, whereas MSC-EVs ameliorate retinal apoptosis and oxidative stress by transporting neuronal precursor cell-expressed developmentally downregulated 4 (NEDD4) to cause PTEN ubiquitination and degradation and activate downstream AKT/NRF2 pathway [ 95 ]. The knockdown of NEDD4 significantly impairs the retinal protective potential of MSC-EVs.…”
Section: Natural Msc-evs In the Treatment Of Dm And Diabetic Complica...mentioning
confidence: 99%